Using Multiple Criteria Techniques to Overcome the Uncertainty in Decision-Making and Selection of Control Priorities in Power Plant Industries - Elahe KAZEMI; Taleb ASKARIPOOR; Mostafa MARZBAN (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: In developing countries, multiple criteria decision-making techniques are important ways to overcome financial, human and information restrictions, and the elimination of existing conflicts in the selection of appropriate solutions in order to increase the level of safety and improve productivity. The aim of this study was to determine and compare the risk calculated by the two methods of multi-criteria decision-making including, TOPSIS and measure of belief approach in fuzzy logic concepts to resolve doubts in selection of control priorities. Methods: In order to identify hazards, the documentation review, interviews with experts, brainstorming sessions, knowledge and experience group of experts in occupational health and safety engineering were used. Then, the real risks of identified hazards were determined using TOPSIS and measure of belief approach in fuzzy logic. Results: In the present study, according to TOPSIS, falling in tanks, reservoirs, and canals with the relative closeness 0.7439 ranked in the first place and explosion with the relative closeness 0.5769 had the second place. Furthermore, in the fuzzy method, firing gas turbines and breakage of high pressure steam pipes, with the measure of belief 0.6, ranked in the first place and falling in tanks, reservoirs, and canals with the measure of belief 0.2 had the second place. The results showed that the two methods have solidarity and are matched in determining the risk of safety hazards in industrial power plants. Conclusion: Using logical and mathematical methods, could manage limited resources and adopting the most appropriate control strategies.